Family Health Tasks and Their Relationship with Childhood Stunting in Primary Healthcare Settings in Indonesia - Isymiarni Syarif (Lembaga Edukasi Ilmiah Indonesia, 2026)
Introduction: Childhood stunting remains a major public health challenge in Indonesia, particularly at the primary care level. Family involvement plays a crucial role in child growth, yet empirical evidence on the relationship between family health tasks and stunting is limited. This study aimed to examine the association between family health tasks and childhood stunting in primary care settings in Indonesia. Methods: A quantitative analytical cross-sectional study was conducted among 60 families with children aged 6–59 months attending selected primary healthcare centers. Family health tasks were assessed using a structured questionnaire covering health problem recognition, decision-making, caregiving, home environment management, and healthcare utilization. Childhood stunting was determined using height-for-age z-scores based on World Health Organization growth standards. Data were analyzed using descriptive statistics and chi-square tests. Results: The prevalence of childhood stunting was 40.0%. More than half of the families demonstrated inadequate performance of family health tasks. A statistically significant association was found between family health tasks and childhood stunting, with higher stunting prevalence among children from families with inadequate task performance (p < 0.05). Conclusion: Inadequate family health task performance is associated with an increased risk of childhood stunting. Strengthening family capacity to perform essential health tasks through family-centered interventions in primary care may contribute to more effective stunting prevention strategies in Indonesia.